Investigation of phosphate removal using sulphate-coated zeolite for ion exchange - Choi, Jae-Woo; Hong, Seok-Won; Kim, Dong-Ju; Lee, Sang-Hyup (TAYLOR & FRANCIS LTD, 2012)
Sulphate-coated zeolite (SCZ) was characterized and employed for the removal of phosphate from aqueous solutions using both batch and column tests. Batch experiments were conducted to assess the sulphate dilution ratio, reaction time for coating, surface washing and calcination temperature during the synthesis of SCZ. Langmuir isotherm and pseudo-first-order models were suitable to explain the sorption characteristics of phosphate onto the SCZ. Equilibrium tests showed that SCZ was capable of removing phosphate, with a maximum binding energy beta = 30.2 mg g(-1), compared to other adsorbents, such as activated alumina and ion exchange resin. The Thomas model was applied to the adsorption of phosphate to predict the breakthrough curves and the parameters of a column test. The model was found to be suitable for describing the adsorption process of the dynamic behaviour of the SCZ column. The total adsorbed quantity and equilibrium uptake of phosphate related to the effluent volumes were determined by evaluating the breakthrough curves obtained under the allowed conditions. The results of batch and column experiments, as well as the low cost of the adsorbent, suggested that SCZ could be used as an adsorbent for the efficient and cost-effective removal of phosphate from aqueous solution.